2017
DOI: 10.3389/fmicb.2017.00004
|View full text |Cite
|
Sign up to set email alerts
|

The Active Component of Aspirin, Salicylic Acid, Promotes Staphylococcus aureus Biofilm Formation in a PIA-dependent Manner

Abstract: Aspirin has provided clear benefits to human health. But salicylic acid (SAL) -the main aspirin biometabolite- exerts several effects on eukaryote and prokaryote cells. SAL can affect, for instance, the expression of Staphylococcus aureus virulence factors. SAL can also form complexes with iron cations and it has been shown that different iron chelating molecules diminished the formation of S. aureus biofilm. The aim of this study was to elucidate whether the iron content limitation caused by SAL can modify th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 72 publications
1
39
0
1
Order By: Relevance
“…A recent study demonstrated that salicylic acid (SAL) reduced bacterial adhesion, affected biofilm structural development, reduced viable biomass, extracellular proteins and polysaccharides, and promoted biofilm detachment (12). However, it was observed that the presence of SAL, the active component of aspirin, exhibited moderate iron-chelating capacity, which markedly promoted Staphylococcus aureus biofilm production (13). These different observations may have been due to differences in the experiment design, model use and aspirin concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated that salicylic acid (SAL) reduced bacterial adhesion, affected biofilm structural development, reduced viable biomass, extracellular proteins and polysaccharides, and promoted biofilm detachment (12). However, it was observed that the presence of SAL, the active component of aspirin, exhibited moderate iron-chelating capacity, which markedly promoted Staphylococcus aureus biofilm production (13). These different observations may have been due to differences in the experiment design, model use and aspirin concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Ethanolic extracts of the carotenoid pigment from bacterial suspensions with equal optical density (OD) at 600 nm were quantified spectrophotometrically at 450 nm 63 . The quantitative assessment of biofilm formation was performed as previously described with modifications 64 . Briefly, S. aureus strains were grown for 18 h and diluted 1:100 in TSB supplemented with 0.25% of glucose (TSBg).…”
Section: Methodsmentioning
confidence: 99%
“…Three independent experiments were performed in sixtuplicate measurements. PIA production was assessed by ELISA according to a protocol described elsewhere 64 . Briefly, the procedure was similar to that described above for biofilm except that, after blocking solution removal,100 μl per well was added of a 75 ng/ml wheat germ agglutinin (WGA)-HRP conjugate, a lectin that binds to PIA sugar residues.…”
Section: Methodsmentioning
confidence: 99%
“…Biofilm formation was quantitatively assessed according to a procedure routinely performed in our laboratory (Dotto et al, 2017 ). Briefly, S. aureus suspensions were placed in sterile 96-well polystyrene microtiter plates.…”
Section: Methodsmentioning
confidence: 99%